Pengalaman Melaksanakan Pencegahan Transmisi COVID-19 pada Lansia - Maria Lambertina Barek Aran; Yuliani Pitang; Anggia Riske Wijayanti (Jurnal Keperawatan Muhammadiyah, 2022)
Objective : The purpose of research with a phenomenological approach is to explain what experiences people experience in this life, including interactions with other peopleMethods : This study uses a qualitative method with a phenomenological approach. Qualitative research is research conducted to obtain answers or in-depth information about a person's opinions, feelings, which may be obtained about attitudes, beliefs, desires, and behavior as the target population.Result : The results of the study obtained 6 themes, namely knowledge about COVID-19, the psychological impact felt by families, preparation for preventing COVID-19 transmission, Implementation of preventing transmission of COVID-19 , Obstacles in the implementation of preventing the transmission of COVID-19 and, the need for information.Conclusions: Based on the results of the study, it can provide some descriptions of the experiences of the elderly in preventing the transmission of COVID-19 with the conclusion that all informants agree that COVID-19 is a disease caused by a virus that attacks the respiratory system. with the most severe complications, namely death